Biomechanical analysis of the snatch technique for elite and varsity weightlifters - Arauz, P. G.; Garcia, G.; Llerena, J. (Journal of Biomechanics, 2024)
Understanding the importance of movement asymmetries and variations in technique proficiency across different level of weightlifters is crucial. The purpose of this study was to examine differences in joint kinematics, muscle activation, and barbell parameters between elite and varsity weightlifters during the snatch utilizing integrated 3D motion capture and EMG systems. In addition, it analyzes symmetries in joint kinematics and muscle activation in both groups. Ten female participants, comprising 5 elite and 5 varsity weightlifters, along with thirteen male participants, consisting of 6 elite and 7 varsity weightlifters during snatch were measured. Several asymmetries in posture and muscle activation were identified in both elite and varsity weightlifters. In addition, elite weightlifters exhibited significantly more flexed knees than varsity counterparts (p < 0.05) at the conclusion of the second pull and at the highest position of the barbell. Furthermore, significantly lower activity in gluteus maximus was detected in elite weightlifter at the highest point of the barbell than in the varsity groups (p < 0.05). Moreover, elite males achieved a lower maximum height for the barbell compared to varsity males (p = 0.006). Furthermore, elite females demonstrated less horizontal displacement (D2x) (p = 0.005) than varsity counterparts. Varsity women presented significantly lower horizontal velocity (p = 0.003) at the conclusion of the second pull than varsity counterparts. Despite several asymmetries detected, those may not be critical factors in achieving a successful snatch lift, given that all weightlifters successfully completed the lift. However, variations in posture and muscle activation may still be associated with improvements in technique proficiency across different levels of weightlifters.